Research and Responsibility in Global Health: An Analysis of the Joining Forces Study in Ghana - Taylor, Lauren (Kennedy Institute of Ethics journal, 2020)
, ABSTRACT:, We explore conceptions of responsibility and integrity in global health research and practice as it is being carried out in the academic setting. Our specific motivation derives from the recent publication of a study by a clinical research team involving the delivery of mental health care services in a Ghanaian prayer camp. The study was controversial on account of the prayer camp's history of human rights abuses and therefore was met with several high-profile critiques. We offer a more charitable evaluation of the Joining Forces study. Our analysis has three primary goals. First, we respond to criticism suggesting that the Joining Forces research team needed to maintain some form of morally "clean hands" in relation to the human rights abuses at Mount Horeb prayer camp. We argue that, for academic global health practitioners working under severe resource constraints, what is reasonable and responsible to pursue is a complex proposition without a one-size-fits-all ethical answer. Second, we offer an explanation for why the Joining Forces study team designed the project as they did in spite of their obvious vulnerability to ethical concern. We argue that the Joining Forces study was a morally risky, but ethically earnest effort to reach a neglected patient population and promote behavior change in prayer camp staff. Third, we identify an open ethical question born of the researchers' commitment to pragmatism that, to our knowledge, has not been previously addressed in published discussion of the Joining Forces project. Namely, was the incomplete disclosure of information to prayer camp staff defensible? We close with a broader reflection on the notion of moral integrity in the pursuit of the salutary aims of global health.